A methods engineering study on Kian Heng Corporation - Daos, Darwyn (College of Engineering, 2004)
Kian Heng Trading Corporation is a company based in the Philippines that offers toll manufacturing, warehousing and trucking services. It has begun its operations as a sister company of a more established and bigger company, Alcos Global Corporation. Some of Kian Heng's major clients include some of the country's leading companies such as Unilever, SC & Johnson, Makro and Glaxo Smithkline. The General Manager, Mr. Paul Sy, requested the researchers to focus specifically on the toll manufacturing branch of the company. Two main operations fall under this branch namely repacking and bundling services. The researchers, equipped with methods engineering ideas, are tasked to identify possible areas for improvement in the specified branch and formulate viable methods to bring about the desired improvement. Data gathering was done primarily through interviews with the manager, supervisors and employees as well as intent observations on the processes and system framework of the company. The researchers also referred to company records and documents for other data such as monthly production reports and company profile. With the use of methods engineering exploratory tools, the researchers identified four core problems which are poor workplace layout, poor workplace design, poor system and lack of records and poor work design. These problems along with their causes were summarized in a DTV diagram to serve as a clear guide in the formulation of solutions to the problem. Furthermore, with the use of Pareto analysis, the scope of the study was established to cover two products under repacking - Glade Touch and Fresh (GT & F) and Baygon Laminated Mats - and the bundling process. For the first problem, the researchers came up with a solution to locate the whole task in one table. It is designed to decrease material handling and help increase production. With the use of a decision table and value engineering, it was chosen with the benefit and less cost and attainment of must objectives. Meanwhile, the researchers found that the addition of chairs in machine operation and adjustment of the height of the currently used monobloc chairs are the best actions to take to reduce the work related discomforts and possible diseases. On the other hand, for poor system and lack of records, the researchers came up with the alternative to sort the files according to product and to change the Daily Packaging Forms to provide ease in recording, accessibility of information and easy maintenance. Lastly, the fourth problem refers to poor work design where the guiding objective in the formulation of these alternatives was to determine the production capacities of the workers for the product lines under study in order to establish a guide for production schedule. The concept of Line balancing was the primary tool that has been used by the researchers in the formulation of alternatives under this area. The alternative chosen uses one day, specifically Mondays, for the first three operations of Touch and Fresh Production, Thursdays for Makro Production, and the rest of the week for production of Bagyon Laminated Mats and of the rest of production of Touch and Fresh. The alternative will result increased productivity, reduced idle time, standardized daily and weekly quota, decreased delayed and rushed production and decreased deliberate delay of movements, was chosen. In consonance of this, the chosen alternative also ranked highest in the value engineering which included the want objectives namely highest productivity, highest efficiency of the assembly line and lesser workstation shifts.